Assessment of lupus: where are we now?. Issue 3 (March 1993) - Hay, E; Gordon, C; Emery, P
Abstract : Decisions about treatment for patients with SLE are based on numerous criteria, including the rate of change of clinical features and disease markers (especially antibodies to dsDNA and markers of complement turnover), which organ systems are affected, the severity of manifestations, and the presence of pre-existing damage (which may reduce the reserve capacity of the organ system). Most of the currently available organ systems calculate a single overall score, at a single point in time, and take few of these considerations into account. SLAM is the only index to consider directly the scoring of severity as well as activity, though this concept is probably inherent in most of the other indices because of various methods for weighting the scores. Preliminary studies have indicated that four of the scales (BILAG, SLAM, LAI, and SLEDAI) are sensitive to change. Few of the indices have been tested longitudinally, hence their role in clinical trials remains to be established. None of the indices considers the impact of damage, indeed this is not their remit, but this concept is being considered by an international working group. Outcome in SLE has been shown to be determined by, among other things, the number of exacerbations and the presence of renal or neurological disease. It would seem, therefore, important to measure disease activity in designated organ systems, which most of the indices fail to do. The inclusion of immunological tests in some scales (for example, SIS, SLEDAI, LAI) makes them unsuitable for use as instruments to validate immunological or other scatological markers. Furthermore, given the heterogeneity of disease manifestations in SLE, and evidence linking scatological abnormalities with specific clinical manifestations, it is perhaps naive to expect a new scatological test to correlate strongly with overall disease activity. Three of the currently available activity scales have been shown to be reliable, both between and within raters (BILAG, SLAM, SLEDAI). The lack of a 'gold standard' for measuring disease activity in SLE makes it difficult to be sure that these scales are actually measuring what they are supposed to be measuring (criterion validity), but they do correlate strongly with each other in cross sectional studies, suggesting that they are, at least, all measuring the same thing (convergent validity). Convergent validity for these instruments used longitudinally remains to be established, particularly for patients with very active disease. In conclusion, measurement of disease activity in SLE is central to patient care, and a number of instruments are available fro this purpose. Although none is perfect, most are reliable and valid, and are suitable for classifying and monitoring groups of patients in the research setting. In reality, the indices are used with the additional benefit of laboratory markers and, as yet, no one has found the instruments sufficiently sensitive and specific to rely entirely upon them. The exact choice of instrument should be governed by the purpose for which it is required in clinical practice. Disease activity scales are unlikely to be appropriate for dictating treatment decisions in individual cases. An instrument which would be comprehensive and flexible enough for this purpose would necessarily prove too complicated and cumbersome for widespread use.